Leprosy on Reunion Island, 2005-2013: Situation and Perspectives. - Guillaume Camuset; Sophie Lafarge; Gianandrea Borgherini; Anne Gerber; Nicolas Pouderoux; Aurélie Foucher; Patrice Poubeau; Rodolphe Manaquin; Sophie Larrieu; Pascal Vilain; Laetitita Huiart (Public Library of Science (PLoS), 2016)
BACKGROUND:Reunion Island is a French overseas territory located in the south-western of Indian Ocean, 700 km east of Madagascar. Leprosy first arrived on Reunion Island in the early 1700s with the African slaves and immigration from Madagascar. The disease was endemic until 1980 but improvement of health care and life conditions of inhabitants in the island have allowed a strong decrease in new cases of leprosy. However, the reintroduction of the disease by migrants from endemic neighbouring countries like Comoros and Madagascar is a real and continuing risk. This observational study was then conducted to measure the number of new cases detected annually on Reunion Island between 2005 and 2013, and to describe the clinical features of these patients. METHODOLOGY/PRINCIPAL FINDINGS:Data were collected over two distinct periods. Incident cases between 2005 and 2010 come from a retrospective study conducted in 2010 by the regional Office of French Institute for Public Health Surveillance (CIRE of Indian Ocean), when no surveillance system exist. Cases between 2011 and 2013 come from a prospective collection of all new cases, following the implementation of systematic notification of all new cases. All patient data were anonymized. Among the 25 new cases, 12 are Reunion Island residents who never lived outside Reunion Island, and hence are considered to be confirmed autochthonous patients. Registered prevalence in 2014 was 0.05 /10 000 habitants, less than the WHO's eradication goal (1/10 000). CONCLUSIONS/SIGNIFICANCE:Leprosy is no longer a major public health problem on Reunion Island, as its low prevalence rate indicates. However, the risk of recrudescence of the disease and of renewed autochthonous transmission remains real. In this context, active case detection must be pursued through the active declaration and rapid treatment of all new cases.